2021
DOI: 10.1002/slct.202102724
|View full text |Cite
|
Sign up to set email alerts
|

Effective Enhancement of the Second‐Order Nonlinear Optical Responses of Graphynes by Introducing π‐Conjugated Chains with Donor/Acceptor Groups

Abstract: Using density functional theory calculations, we have analyzed second-order nonlinear optical (NLO) properties of a series of 1À 6, 9, 12). This type of modification can induce evident electron transfer between the graphyne and conjugated chain and decrease the transition energy, resulting in the system exhibiting a large static first hyperpolarizability (β 0 ). The β 0 values of the GY[n]À (CH=CH) m À NH 2 /NO 2 show a monotonously increasing trend with lengthening the À (CH=CH) m À NH 2 /NO 2 chain from m = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…We found that the β 0 value of the OM 3 + @GYs – (M = Li, Na, and K) depends on the atomic number of the alkali atom and the pore size of GY . Additionally, functional modification on the edge of graphyne is also an effective strategy to increase its static β 0 value. In our previous study, replacing carbon atoms in the graphdiyne analog with boron or nitrogen atoms can improve the second-order NLO response, where N atom substitution has the best effect …”
Section: Introductionmentioning
confidence: 96%
“…We found that the β 0 value of the OM 3 + @GYs – (M = Li, Na, and K) depends on the atomic number of the alkali atom and the pore size of GY . Additionally, functional modification on the edge of graphyne is also an effective strategy to increase its static β 0 value. In our previous study, replacing carbon atoms in the graphdiyne analog with boron or nitrogen atoms can improve the second-order NLO response, where N atom substitution has the best effect …”
Section: Introductionmentioning
confidence: 96%
“…The doping of heteroatoms modifies the terms V NN and V Ne and the electron occupation modulation modifies the terms V Ne and V ee . Strategies to enhance NLO properties include the increase of π-conjugation length 22 and the introduction of donor and acceptor groups. 23 Moreover, the introduction of heteroatoms, such as boron and nitrogen, into the π-system can change the delocalization of the π-system, and modify the electronic structure of the materials to obtain new electronic properties and functions.…”
Section: Introductionmentioning
confidence: 99%
“…10–12 A key benefit of D–π–A systems versus other NLO materials is that their structures are feasibly modifiable, e.g. , adjusting the strength of the donor/acceptor group 13 or varying the length of π-conjugation, 14 for large intramolecular charge transfer, thus possibly bringing about strong second order NLO responses. Even though these common strategies for tuning the NLO properties in D–π–A push–pull systems may be able to get good NLO responses, there is still much space to further improve the NLO response of D–π–A push–pull molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Among previous studies with various effective strategies to improve the NLO responses of organic molecules, the donor-(p-conjugated bridge)-acceptor (D-p-A) push-pull framework has been a successful paradigm for the design of organic NLO molecular materials. [10][11][12] A key benefit of D-p-A systems versus other NLO materials is that their structures are feasibly modifiable, e.g., adjusting the strength of the donor/acceptor group 13 or varying the length of p-conjugation, 14 for large intramolecular charge transfer, thus possibly bringing about strong second order NLO responses. Even though these common strategies for tuning the NLO properties in D-p-A push-pull systems may be able to get good NLO responses, there is still much space to further improve the NLO response of D-p-A push-pull molecules.…”
Section: Introductionmentioning
confidence: 99%